Assessment of the freshwater fisheries in Muda Lake, Kedah, Malaysia - Lee, Patrick K.Y (WWF-Malaysia, 2013)
This study was conducted as part of WWF-Malaysia's efforts to protect and conserve the Ulu Muda forest complex in Kedah. It aimed to assess the current status of the freshwater fisheries at Muda Lake, which is one of three large man-made reservoirs located in Ulu Muda forest.